Energy Efficient Homes: Ceiling Fans - Kathleen C. Ruppert; Wendell A. Porter; Randal A. Cantrell; Hyun-Jeong Lee; Giovanna Marie Benitez (EDIS)
One of the myths about ceiling fans is that they lower the temperature in a room. Actually, ceiling fans do not lower room temperature. However, they do create a breeze, making room occupants feel cooler and more comfortable. When a ceiling fan is operating, you can usually raise the thermostat setting by up to four degrees during the cooling season with no reduction in comfort. Increasing the room temperature by even two degrees can cut your cooling costs by at least 4%–6%, and in some cases by as much as 8%.